Pembuatan nata de cassava dari limbah cair tapioka dengan menggunakan sumber nitrogen alami yang berbeda - Cory Dian Alfarisi; Yelmida; Ida Zahrina; Anisa Mutamima (Jurnal Ilmiah Pertanian, 2021)
Liquid waste from processing cassava into tapioca starch is carbohydrate-rich waste and can be used as a growth medium for the Acetobacter xylinum, which is useful in producing one of the fermentation products, i.e. nata. Several factors influence the production of nata, one of them is the addition of nutrients in the form of nitrogen in the fermentation medium. The nitrogen source used is usually from inorganic fertilizers, such as urea and ammonium sulfate. In this study, fermentation of tapioca starch wastewater was developed, using a natural sources of nitrogen derived from soybean and green bean sprouts extract. Nata was made by treating various concentrations of soybean and green bean sprouts extract (3%, 4%, 5%) and fermentation time (6 days, 7 days, 8 days, 9 days and 10 days). The characteristics of the nata product were seen from the thickness and yield of the nata. The nata de cassava product's optimum results were tested for thickness, yield, and moisture content. The results showed that the best type of natural nitrogen source was soybean sprouts extract 5%, fermentation time of 10 days with a thickness of 0.55 cm, the water content of 97.58%, and yield of 63.09%